Family Policies in Latin America
XX, 386 p. 42 illus., 29 illus. in color.
Keywords: This book examines family policies in Latin America. The first half of the book adopts a thematic approach to assess how the concept of ‘family’ has changed over the last few decades, and how family policies are intrinsically linked to demographic changes, social class, family arrangements and the labour market. The second half of the book provides detailed country case studies in order to analyse family policies in action. Drawing on evidence from Argentina, Bolivia, Brazil, Chile, Costa Rica, Ecuador, El Salvador, Guatemala, Honduras, Mexico, Nicaragua, Panama, Paraguay, and Uruguay, it offers a comprehensive and comparative overview of family policies across the continent, demonstrating the various ways in which they have been impacted by political regimes and governance. The book also compares family policies in Latin America to those in Europe and North America. It will appeal to all those interested in family policy, public policy, development studies and sociology, as well as Latin America more generally. Natália G. D. Sátyro is Associate Professor in the Department of Political Science, Federal University of Minas Gerais, Brazil. Her research interests include welfare policy, income inequality, and political institutions. Analía Minteguiaga is a Researcher at the National Scientific and Technical Research Council of Argentina (CONICET) and the Gino Germani Research Institute, University of Buenos Aires, Argentina. Her research examines welfare regimes, social protection systems, socio-labor policies and dynamics of (in)equality in Latin America.